Increase in Alcoholic Hepatitis as an Etiology for Liver Transplantation in the United States: A 2004–2018 Analysis. Issue 11 (November 2020) - Noureddin, Nabil; Yang, Ju Dong; Alkhouri, Naim; Noreen, Samantha M.; Toll, Alice E.; Todo, Tsuyoshi; Ayoub, Walid; Kuo, Alexander; Voidonikolas, Georgios; Kotler, Honore G.; Pelphrey, Michalyn D.; Durand, Brenda J.; et al.
Abstract : Background: Changing opinions on the alcohol abstinence requirement have led to increased liver transplantation (LT) for alcoholic hepatitis (AH). We aimed to determine the trend in LT for AH in the United States and overall and graft survival rates. Methods: Adult liver-alone and liver-kidney registrations added to the Organ Procurement and Transplantation Network waiting list between 2004 and 2018 were divided into 3 periods (2004–2009, 2010–2013, 2014–2018). Kaplan-Meier survival models illustrated patient and graft survival. Results: Between 2004 and 2018, 529 AH patients were registered for and 254 received LT. By periods, 116, 73, and 340 patients were registered for and 49, 17, and 188 patients received LT, respectively, indicating a increase in LT for AH from 2014 to 2018. Yearly registrants from 2014 to 2018 were 32, 47, 51, 70, and 140, and recipients were 16, 24, 24, 38, and 88, respectively, indicating increases of 338% and 450% in registrants and recipients, respectively, since 2014. AH patients had the highest 1- and 3-year posttransplant survival (93.2% and 87.3%, respectively) and graft survival (90.4% and 84.8%, respectively) comparing to other LT recipients. Conclusions: LT for AH in the United States is at an all-time high with an increased overall patient and graft survival.